Influence of Digital Trends and Behavioral Financial on Investment in Sharia Capital Market - Amin Setiyadi; Tri Setyorini; Heni Noviarita (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
It was found that fraudulent investments that cost the state Rp. 114.9 trillion and the level of financial literacy in 2019 in the Province. This study aims to determine how digital trends and financial behavior affect investment interest in Islamic economics master students at UIN Raden Intan Lampung. The research population is postgraduate students of the Islamic economics study program at UIN Raden Intan Lampung batch 2019, 2020, 2021. The sample used is a saturated sample with a sample of 60 respondents. Hypothesis testing uses data analysis techniques using the SPSS version 22 application. The findings of this study are digital trends (X1) and financial behavior (X2) simultaneously (together) affect investment interest (Y) or have a significant meaning.